Photocatalytic degradation of p-nitrophenol and methylene blue using Zn-TCPP/Ag doped mesoporous TiO2 under UV and visible light irradiation. Issue 53 (13th November 2016) - Rabbani, Mahboubeh; Bathaee, Hamideh; Rahimi, Rahmatollah; Maleki, Ali
Abstract: In this study, Ag-doped mesoporous TiO2 powder was prepared via a sol–gel route with Pluronic P123 as template and then was modified with zinc(II) tetrakis(4-carboxyphenyl)porphyrin. The catalysts were characterized by X-ray diffraction, diffuse reflectance spectroscopy, Fourier transform infrared (FT-IR), scanning electron microscopy, N2 sorption experiments (BET), X-ray fluorescence analysis, and inductively coupled plasma spectroscopy. The photocatalytic activities of Ag-doped mesoporous TiO2 and Zn-TCPP/Ag-doped mesoporous TiO2 were evaluated using methylene blue and p -nitrophenol as pollutant compounds under UV and visible light irradiation. The results show that Zn-TCPP/Ag-doped mesoporous TiO2 have higher activity than Ag-doped mesoporous TiO2 under visible light irradiation, but its activity is lower under UV light irradiation.